Simulating nature : a philosophical study of computer-simulation uncertainties and their role in climate science and policy advice - Petersen, Arthur C. (Arthur Caesar), 1970- (Chapman and Hall/CRC, 2012)
Computer simulation has become an important means for obtaining knowledge about nature. The practice of scientific simulation and the frequent use of uncertain simulation results in public policy raise a wide range of philosophical questions. Most prominently highlighted is the field of anthropogenic climate change-are humans currently changing the.